Pengaruh Disiplin Kerja, Komitmen Organisasional dan Motivasi Kerja terhadap Kinerja Karyawan Bank Prisma Dana Sulawesi Utara - Dame, Benny; Rumawas, Wehelmina; Waworundeng, Welly (JURNAL ADMINISTRASI BISNIS (JAB), 2021)
Employee performance is seen from what he does and "provides" work that is in accordance with what has become the goal of the organization or company where he works. Thus the problem of employee performance becomes a very "urgent" concern in any organization, both government organizations and private companies that need very serious handling. This study aims to analyze the effect of work discipline, organizational commitment, and work motivation on employee performance. Sampling using proportional random sampling method, data obtained by using a questionnaire to 67 respondents at the Prisma Dana Bank of North Sulawesi. The data were analyzed using a structural equation model with the help of the SmartPLS 3 application. The results show that work discipline has a positive and significant effect on employee performance, work discipline has a positive and significant effect on work motivation, organizational commitment has a positive and significant effect on work motivation, organizational commitment has a positive and significant effect on work motivation, and work motivation has a positive and significant effect on employee performance.